Patient responses to research recruitment and follow-up surveys: findings from a diverse multicultural health care setting in Qatar. Issue 1 (December 2016) - Khidir, Amal; Asad, Humna; Abdelrahim, Huda; Elnashar, Maha; Killawi, Amal; Hammoud, Maya; Al-Khal, Abdul; Haddad, Pascale; Fetters, Michael
Abstract Background Health care researchers working in the Arabian Gulf need information on how to optimize recruitment and retention of study participants in extremely culturally diverse settings. Implemented in Doha, Qatar in 2012 with 4 language groups, namely Arabic, English, Hindi, and Urdu, this research documents persons' responses to recruitment, consent, follow-up, and reminder procedures during psychometric testing of the Multicultural Assessment Instrument (MAI), a novel self- or interviewer-administered survey. Methods Bilingual research assistants recruited adults in outpatient clinics by approaching persons in particular who appeared to be from a target language group. Participants completed the MAI, a second acculturation instrument used for content-validity assessment, and a demographics questionnaire. Participants were asked to take the MAI again in 2–3 weeks, in person or by post, to assess test-retest reliability. Recruitment data were analyzed by using nonparametric statistics. Results Of 1503 persons approached during recruitment, 400 enrolled (27 %)—100 per language group. The enrollment rates in the language groups were: Arabic-32 %; English-33 %; Hindi-18 %; Urdu-30 %. The groups varied somewhat in their preferences regarding consent procedure, follow-up survey administration, contact mode for follow-up reminders, and disclosure of personal mailing address (for postal follow-up). Over all, telephone was the preferred medium for follow-up reminders. Of 64 persons who accepted a research assistant's invitation for in-person follow-up, 40 participants completed the interview (follow-up rate, 63 %); among 126 persons in the postal group with a deliverable address, 29 participants mailed back a completed follow-up survey (response rate, 23 %). Conclusions Researchers in the Arabian Gulf face challenges to successfully identify, enroll, and retain eligible study participants. Although bilingual assistants—often from the persons' own culture—recruited face-to-face, and our questionnaire contained no health care-related content, many persons were reluctant to participate. This occurrence was observed especially at follow-up, particularly among participants who had agreed to follow-up by post.